Analysis and Selection of the Optimal Pump Laser Power Density for SERF Co-Magnetometer Used in Rotation Sensing - Kai Zhang; Linlin Yuan; Ze Cai; Hang Gao; Rui Wang; Pengcheng Du; Xinxiu Zhou (Photonics, 2024)
This paper systematically studies the output noise model of the K-Rb-21Ne co-magnetometer and proposes the method for determining the optimal pump laser power density. The amplitude-frequency response and the equivalent model for each frequency band are obtained through the transfer function of the co-magnetometer. Based on the established model and considering the power spectral density characteristics of magnetic noise, the output noise equation is formulated. Consequently, the pump laser power density yielding minimal output noise is determined. Both experimental and simulation results indicate that the pump laser power density yielding minimal output noise is greater than the pump laser power density corresponding to the maximum scale factor. Moreover, when the co-magnetometer operates at the pump laser power density corresponding to the minimal output noise, the output noise can be reduced by approximately 25%, and the Allan variance reaches its optimal value. The optimal Allan variance at 180 °C and 190 °C are 0.01395°/h @100 s and 0.01329°/h @100 s, respectively. Therefore, this pump laser power density is designated as the optimal pump laser power density for the co-magnetometer. Finally, simulations are conducted to investigate the variation patterns of the optimal pump laser power density points and the minimum output noise under different density ratios and gas pressures. The theories and methods proposed in this paper provide significant reference value for selecting the optimal pump laser power density and suppressing magnetic noise in co-magnetometers.